On the gradable nature of the search domain: A study of degree modifiers and the scalar semantics of Finnish spatial grams - Huumo Tuomas (Netherlands, 2022)
Degree modifiers (DM) are intensifying words that typically modify adjectives or adverbs. Some DMs (e.g., ‘rather’, ‘very’) indicate an open scale, which is unbounded and has no maximal or minimal boundaries, others (e.g., ‘quite’, ‘almost’) a closed scale, which has either or both. In Finnish, many spatial grams, i.e., adpositions and adverbs, accept DMs. Such grams have a scalar meaning, which the DM then elaborates. I analyze three groups of grams: 1) topological luona ’at; by’, lähellä ’near’, and kaukana ‘far’; 2) directional kohti ’towards’ and ohi ’past’; and 3) targeting keskellä ‘in the middle of’. I argue that the scalar meaning of the grams may relate 1) to the distance between Figure and Ground; 2) to the direction of Figure’s motion or orientation with respect to Ground; 3) to the precision of Figure’s location at (or deviation from) a targeting point specified with respect to Ground. Most of the grams accept only closed-scale DMs, while some accept open-scale DMs, and yet others both. The compatibility of closed-scale DMs with most of the grams indicates that the search domain of the grams is typically bounded and has at least a maximal-degree boundary and often also a minimal-degree boundary.